2018
DOI: 10.1016/j.toxicon.2018.06.067
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity and pathophysiology of palytoxin congeners after intraperitoneal and aerosol administration in rats

Abstract: Preparations of palytoxin (PLTX, derived from Japanese Palythoa tuberculosa) and the congeners 42-OH-PLTX (from Hawaiian P. toxica) and ovatoxin-a (isolated from a Japanese strain of Ostreopsis ovata), as well as a 50:50 mixture of PLTX and 42-OH-PLTX derived from Hawaiian P. tuberculosa were characterized as to their concentration, composition, in-vitro potency and interaction with an anti-PLTX monoclonal antibody (mAb), after which they were evaluated for lethality and tissue histopathology after intraperito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 36 publications
2
10
1
Order By: Relevance
“…Poli et al (2018) have reported differences of toxicity between PLTX and some of its analogs (42-OH-PLTX and OVTXa) by exposing rats to these toxins trough intraperitoneal routes and aerosol exposures and confirmed results already published by others colleagues (Tubaro et al, 2011;Ciminiello et al, 2013). noted huge differences of toxicity between OVTX a and PLTX: OVTX-a is 10 to 100 times less potent than the other but data obtained by Poli et al (2018) showed only minimal differences. Such differences could explain the difficulties to compare toxin analogs concentrations from NW Mediterranean and Adriatic strains.…”
Section: Isolation and Toxicity Evaluation Of The Different Pltx Analogssupporting
confidence: 77%
See 1 more Smart Citation
“…Poli et al (2018) have reported differences of toxicity between PLTX and some of its analogs (42-OH-PLTX and OVTXa) by exposing rats to these toxins trough intraperitoneal routes and aerosol exposures and confirmed results already published by others colleagues (Tubaro et al, 2011;Ciminiello et al, 2013). noted huge differences of toxicity between OVTX a and PLTX: OVTX-a is 10 to 100 times less potent than the other but data obtained by Poli et al (2018) showed only minimal differences. Such differences could explain the difficulties to compare toxin analogs concentrations from NW Mediterranean and Adriatic strains.…”
Section: Isolation and Toxicity Evaluation Of The Different Pltx Analogssupporting
confidence: 77%
“…More recently, high purity PLTX administration in mice showed that toxicity is dependent upon the route of administration (Munday, 2011). Poli et al (2018) characterized the toxicity and basic histopathological effects of PLTX (derived from Japanese Palythoa tuberculosa), the analog 42-OH-PLTX (from Hawaiian P. toxica) and ovatoxin-a (isolated from a Japanese strain of Ostreopsis ovata) after intraperitoneal and aerosol administration to rats. All toxin preparations showed similar potency towards mouse erythrocytes in the erythrocyte hemolysis assay and interactions with the anti-PLTX mAb (antibody).…”
Section: Toxicity On Mammalian Cells and Mode Of Actionmentioning
confidence: 99%
“…Toxicity may result from the production of palytoxin-like molecules, a family of highly potent marine toxins (Poli et al, 2018) including isobaric palytoxin (isob-PLTX) and more than a dozen ovatoxins (OVTX-a to -l) (Ciminiello et al, 2008;Ciminiello et al, 2010;Ciminiello et al, 2012a;Ciminiello et al, 2012b;Brissard et al, 2015;García-Altares et al, 2015;Tartaglione et al, 2016;Tartaglione et al, 2017). OVTXs are produced by both O. cf.…”
Section: Different Time Windows Of Blooms Can Be Observed In the Northwestmentioning
confidence: 99%
“…Only a few of these analogues have been studied from a biological and chemical point of view, including (i) 42-hydroxy-PLTX (42 S -OH-50 S -PLTX), isolated from P. toxica [ 2 , 17 ], and its stereoisomer (42 S -OH-50 R -PLTX), isolated from P. tuberculosa [ 3 ]; (ii) ostreocin-D (OST-D) and its analogues, produced by Ostreopsis siamensis [ 11 , 18 , 19 , 20 ]; and (iii) ovatoxin-a (OVTX-a), the most abundant PLTX analogue, produced by Ostreopsis cf. ovata in the Mediterranean Sea [ 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%